2010
DOI: 10.1371/journal.pone.0013884
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Male Infertility Is Strongly Associated with Aberrant Promoter Methylation of Methylenetetrahydrofolate Reductase (MTHFR)

Abstract: BackgroundAbnormal germline DNA methylation in males has been proposed as a possible mechanism compromising spermatogenesis of some men currently diagnosed with idiopathic infertility. Previous studies have been focused on imprinted genes with DNA methylation in poor quality human sperms. However, recent but limited data have revealed that sperm methylation abnormalities may involve large numbers of genes or shown that genes that are not imprinted are also affected.Methodology/Principal FindingsUsing the methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 30 publications
1
83
1
1
Order By: Relevance
“…Khazamipour and colleagues were the pioneering group who investigated the methylation profiles of MTHFR gene in NOA infertile patients and reported a significant association between methylation status MTHFR gene and infertility in azoospermic males [54]. Recently, DNA methylation aberrations of MTHFR gene promoter in paternal spermatozoa were described in small cohorts of oligozoospermic men and in patients with poor sperm morphology and recurrent spontaneous aberrations [49,55,61] (Table 1). However, in our study, we did not observe a significant association between methylation profiles of MTHFR gene, neither in patients with NOA nor in patients with oligozoospermia, in a Turkish population (Kulaç et al, unpublished data).…”
Section: Methylation Of Imprinted Genesmentioning
confidence: 99%
“…Khazamipour and colleagues were the pioneering group who investigated the methylation profiles of MTHFR gene in NOA infertile patients and reported a significant association between methylation status MTHFR gene and infertility in azoospermic males [54]. Recently, DNA methylation aberrations of MTHFR gene promoter in paternal spermatozoa were described in small cohorts of oligozoospermic men and in patients with poor sperm morphology and recurrent spontaneous aberrations [49,55,61] (Table 1). However, in our study, we did not observe a significant association between methylation profiles of MTHFR gene, neither in patients with NOA nor in patients with oligozoospermia, in a Turkish population (Kulaç et al, unpublished data).…”
Section: Methylation Of Imprinted Genesmentioning
confidence: 99%
“…In another study by Khazamipour et al, [153], 53 % of men with nonobstructive azoospermia revealed hypermethylation of the MTHFR promoter, while none of the men with obstructive azoospermia exhibited hypermethylation of this gene promoter, suggesting that MTHFR hypermethylation is a specific epigenetic aberration that may specifically contribute to certain types of male infertility. In addition, Wu et al, [154] in a study reported that hypermethylation of MTHFR gene promoter in sperm was associated with idiopathic male infertility. Abnormal DNA methylation of H19 and MEST imprinted genes has also been shown to be associated with oligozoospermia [140], suggesting that spermatogenesis may be particularly vulnerable to changes in the methyl pool brought about by deficiency in MTHFR enzyme.…”
Section: Epigenetic Modifications and Male Infertilitymentioning
confidence: 99%
“…Figure 2 shows the pictorial representation of CpG island frequencies in all three study groups. CpG island methylation frequencies has been associated with maternal risk for DS progeny (21,22,23). Several congenital complications are reported in an individual with DS.…”
Section: Resultsmentioning
confidence: 99%